Prevention Strategies for the Crime of Adultery in the Light of Islamic Law - Abdulrahman, Manswab Mahsen; Awadh, Ali Hemed; Akasi, Hasan Yusuf; Abdalla, Abdulatwif Ibrahim; Chui, Khadija (Jurnal Syariah dan Hukum Komparatif, 2024)
Adultery is a serious offense which is prohibited in Islam. Adultery may cause a lot of repercussions, among them sexually transmitted infections (STIs), also referred to as sexually transmitted diseases (STDs). These infections are sexually transmitted through vaginal, anal, and oral. The significance of the research emerged due to a large number of deaths emanating from HIV/AIDS and other infectious diseases caused by adultery; for example, statistically, about 374 million people living with STIs and more than 1 million sexually transmitted infections (STIs) are acquired every day worldwide. A qualitative data analysis has been deployed in this study that has been gathered from a variety of sources, they include books, journal articles, reports, conference papers, and websites. The information has been analyzed through an explanatory research approach by providing scholars’ opinions and their arguments on the subject matter. Most importantly, this research has established that Islam indeed has put in place some preventive measures to reduce the risk of multi-crimes occurring and their potential harmful effects on individuals and the society at large, and more so, in reference to our study including: self-accountability, lowering the gaze (by shifting away on what is illegal to look at), meet with a non-mahram woman in privacy, shaking hands with a non-mahram woman, tabarruj (make-up grooming), command women to stay at home, wear Hijab for modesty and chastity, indulge in marriage and accept polygamy, impose penalty for adulterous disobedient, among others. In this regard, it is therefore, recommended to implement the preventive strategies set by Islam for the crime of adultery to uphold societal mortality and preserve the wellbeing of the society at a broader spectrum.